Perinatal brain injury in infants with depressed EEG activities immediately after birth - Hayakawa, F; Okumura, A; Kuno, K; Watanabe, K (No to hattatsu, 1996)
We investigated the developmental outcome and features of brain imaging in 33 infants with moderate or severe depression of background EEG activities immediately after birth. Lesions due to perinatal injury were observed in 25 infants on neonatal ultrasonography and/or childhood MRI. These findings strongly correlated with their gestational age. Periventricular leukomalacia and posthermorrhagic porencephaly were observed in preterm infants. On the other hand, perinatal injury of mature brain type, such as multicystic encephalomalacia, parasagittal infarct, bilateral basal ganglia/thalamic lesion, and subcortical leukomalacia, were observed in full-term infants. Periventricular leukomalacia rather correlated with moderate depression of EEG activities than severe depression like observed in full-term neonates who have brain lesions due to perinatal asphyxia.